Early Marriage and Maternal History with Stunted Children Aged 24-59 Months in Mataram City - Rosyida, Rufaida; Widyaningsih, Vitri; Nurwati, Ida (Al-Sihah : The Public Health Science Journal, 2023)
The prevalence of stunting among children in 2021 and 2022 was 25.3% and 24.4% respectively, according to Indonesian Nutritional Status Survey in Mataram City. The Religious Court of NTB Province reported that the rate of early marriage among children was 16.59%. Therefore, this study aimed to analyze the relationship between early marriage and pregnancy history with stunted children in Mataram City. An analytical survey method was used with a case-control design, questionnaire, and anthropometric measurements conducted in a single session. The samples were selected using cluster random sampling, reaching 61 children aged 24-59 months for normal and stunted groups. The results showed that the samples were predominantly male, while increased weight during pregnancy <10 kg (p=0.009, OR=2.948, CI=1.285-6.766) and maternal height <150 cm (p=0.004, OR=2.937, CI=1.406-6.135) were associated with the incidence of stunted children. On the other hand, early marriage (p=0.926, CI=1.31) had no significant relationship with the incidence of stunting. A history of pregnancy and early marriage simultaneously influenced stunting by 30.5%, with the highest predictor being the height of the mother. Therefore, pregnancy history greatly influenced the incidence of stunting among children in Mataram City.